2011
DOI: 10.1038/leu.2011.148
|View full text |Cite
|
Sign up to set email alerts
|

SB1518, a novel macrocyclic pyrimidine-based JAK2 inhibitor for the treatment of myeloid and lymphoid malignancies

Abstract: SB1518 is an innovative pyrimidine-based macrocycle that shows a unique kinase profile with selective inhibition of Janus Kinase-2 (JAK2; IC 50 ¼ 23 and 19 nM for JAK2 WT and JAK2 V617F , respectively) within the JAK family (IC 50 ¼ 1280, 520 and 50 nM for JAK1, JK3 and TYK2, respectively) and fms-like tyrosine kinase-3 (FLT3; IC 50 ¼ 22 nM). SB1518 shows potent effects on cellular JAK/STAT pathways, inhibiting tyrosine phosphorylation on JAK2 (Y221) and downstream STATs. As a consequence SB1518 has potent ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
144
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 35 publications
12
144
0
Order By: Relevance
“…3A). Multiple JAK2 inhibitors have been previously reported to show similar results where they directly target JAK2 but increase or do not affect JAK2 phosphorylation levels (44,45). GinA markedly inhibited S6 phosphorylation dose-dependently in both EJ and HCT116 cells (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…3A). Multiple JAK2 inhibitors have been previously reported to show similar results where they directly target JAK2 but increase or do not affect JAK2 phosphorylation levels (44,45). GinA markedly inhibited S6 phosphorylation dose-dependently in both EJ and HCT116 cells (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Previous studies have also reported multiple JAK2 inhibitors that maintained or increased the phosphorylation levels of JAK2 (44,45). In addition, inhibitors for other kinases have been shown to not affect the phosphorylation levels of the target kinase, whereas the activity was inhibited by the compounds (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…macrocycles discovered in the S*BIO kinase inhibitor program (30,31). As shown in Supplemental Table I, its potency against JAK2 (IC 50 = 46 nM) was achieved with good selectivity against JAK1 and JAK3 (.60-fold) and 5-fold difference against TYK2 (IC 50 = 230 nM).…”
Section: Resultsmentioning
confidence: 95%
“…Studies of this type have ascribed a role for JAK2 dependency in cancer subtypes of breast, prostate, multiple myeloma and Bcell lymphomas. [36][37][38][39] We did not observe inhibitory effects of BMS-911543 in various solid tumor or lymphoma cell lines, including the B-cell lymphoma cell line, KARPAS1106, which is reported to have constitutive JAK2 signaling through genetic inactivation of the pathway negative regulator, SOCS1. 28 Unlike MPNs, our results suggest that persistent STAT3/5 activation does not confer JAK2 dependence in these other cancers, and that the lack of selectivity of the inhibitors utilized towards other JAK family members or kinases outside the family may underlie the observed effects.…”
Section: Discussionmentioning
confidence: 92%